Effects of Morphine and Maternal Care on Behaviors and Protein Expression of Male Offspring. (1st July 2021) - Akbarabadi, Ardeshir; Sadat-Shirazi, Mitra-Sadat; Kabbaj, Mohamed; Nouri Zadeh-Tehrani, Setareh; Khalifeh, Solmaz; Pirri, Fardad; Zarrindast, Mohammad-Reza
Highlights: Morphine-exposure ten days before conception induced molecular and behavioral changes in the offspring. Poor maternal caring affected behaviors and induced molecular changes in the brain of the offspring. Maternal care has a prominent role in the offspring's phenotype. Abstract: Genes and environment interact during development to alter gene expression and behavior. Parental morphine exposure before conception has devastating effects on the offspring. In the present study, we evaluated the role of maternal care in the intergenerational effect of maternal morphine exposure. Female rats received morphine or saline for ten days and were drugfree for another ten days. Thereafter, they were allowed to mate with drug-naïve male rats. When pups were born, they were cross-fostered to assess the contribution of maternal care versus morphine effects on the offspring. Adult male offspring were examined for anxiety-like behavior, spatial memory, and obsessive–compulsive-like behavior. To determine the mechanisms underlying the observed behavioral changes, protein levels of acetylated histone H3, BDNF, Trk-B, NMDA subunits, p-CREB, and 5-HT3 R were measured in the brain. Our results indicate that maternal caregiving is impaired in morphine-abstinent mothers. Interestingly, maternal care behaviors were also affected in drug-naïve mothers that raised offspring of morphine-exposed mothers. In addition, the offspring of morphine abstinent and non-drug dependent mothers, when raised by morphine abstinent mothers, exhibited more anxiety, obsessive–compulsive behaviors and impaired spatial memory. These altered behaviors were associated with alterations in the levels of the above-mentioned proteins. These data illustrate the intergenerational effects of maternal morphine exposure on offspring behaviors. Moreover, exposure to morphine before gestation not only affects maternal care and offspring behavior, but also has negative consequences on behaviors and protein expression in adoptive mothers of affected offspring.